How changes in international trade effect African growth? - Adolfo C. Fernández Puente; Marta Bengoa Calvo; Ana Carrera Poncela (Colegio de Economistas de A Coru\~na, 2009)
The dismal growth performance of Africa in the last decades is one of the main worries of the global economy. In this paper we design an empirical model to explain how the growth rate of the economy is affected by changes in international trade. The main message of the model is that integration enables countries to exchange more varieties of goods and take advantage of some spillovers linked to the export-import process. These predictions are tested using GMM technique in a panel data performed on a sample of 22 countries belonging to the Sub-Sahara region over the period 1970-2002. The estimations suggest that Africa's growth rates are positively related to a more open attitude and to a greater integration in international markets. However, the empirical analysis also points out the need of a certain degree of 'social capacity' to ensure a successful integration. Finally, our results imply that African nations can profit from the economic growth of the OECD countries, as they are the main buyers of the region.
Keywords: 330; international trade; economic growth; panel data estimulation; Wirtschaftswachstum; Außenwirtschaft; Afrika südlich der Sahara